OSCE in Pediatrics - Mittal Manish, Holla RG, Jain Vivek; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2011)
Still in vogue in most postgraduate examinations, covers only a part of the examinee$1 (Bs medical knowledge. The direction that the discussion takes during a case presentation and the level of interrogation depends both upon the examinee$1 (Bs and examiner$1 (Bs approach. This leads to a subjective assessment. Certain areas of clinical pediatrics like interpretation of laboratory and radiological reports, communication skills, problem solving and knowledge of clinical procedures are not tested routinely in the traditional examination. The Objective Structured Clinical Examination (OSCE) attempts to overcome these drawbacks by providing a broad-based format to assess the candidate on multiple aspects of the subject. Objectivity brings with it an element of uniformity. Being structured gives a focus on preparation and assessment. The wide variety of topics inherent to childhood illness provides a delightfully wide source for the examiner to draw upon, but is a nightmare for the candidate. However, there is a silver lining. Being broad based, OSCE gives the candidate an opportunity to make up from an easy question, any marks lost in a station in which he has not scored well. With the introduction of the OSCE system as an integral part of the DNB Pediatrics examination, there was a felt need amongst students for a guide which could help them prepare for the examination. Moreover, the requirement to qualify separately in OSCE in order to receive accreditation made the necessity for such a volume all the more imperative. The book OSCE in Pediatrics is neither meant to cover the whole field of pediatrics nor is it intended to serve as a question bank. It is an effort to sensitize and introduce the student to the OSCE format so that the student can prepare accordingly. The ambit of OSCE extends beyond the examination hall. Preparation for OSCE trains the student to approach a problem in a systematic manner and would certainly help in dealing with the real-life patient.s
Keywords: MCQs and Self-assessment,Pediatrics; Electronic books